Paper 33: Serum and Urine Biomarkers for Treatment Monitoring after Meniscal Allograft Transplantation in a Preclinical Canine Model. Issue 7 (30th July 2022) - Stoker, Aaron; Leary, Emily; Bozynski, Chantelle; Stannard, James; Cook, James; Ewing, Michael
Objectives: To analyze serum and urine biomarker concentrations for their capabilities in delineating differences in assessments of pain and functional outcomes after meniscus allograft transplantation (MAT) in a preclinical canine model. The study was designed to test the hypothesis that serum and urine biomarkers could be used for prognostic (1- and 3-month post-surgical time points) and diagnostic (6-month time point) assessments, based on strong associations with clinically relevant pain and function outcomes after MAT. Methods: Twelve adult, purpose-bred research hounds were included and underwent medial meniscal release (MR) to induce medial compartment gonarthrosis. Three months following MR, medial MAT was performed using: fresh-frozen meniscus (n=4), fresh meniscus (n=4), or fresh menisco-tibial OCA (n=4). Serum and urine from all dogs were collected preoperatively and at 1, 3, and 6 months following MAT. Validated outcome measures for pain, function, effusion, knee range of motion, and gait kinetics were collected at these same timepoints. To develop a prognostic panel of biomarkers, biomarker data from the 1-month and 3-month post-MAT surgery timepoints were used to model 6-month outcomes. A diagnostic panel of biomarkers was developed using biomarker data from the 6-month post-MAT surgery to model 6-month outcomes. Results: Across prognostic biomarker panels, serum biomarkers were mainly represented. A panel including serum IL-6, IL-8, IL-10, and IL-18 had strong model fit for prognostication of the gait kinetics outcome, operated limb %Total Pressure Index (%TPI) (R 2 =.45). Whereas, a biomarker panel including serum CTX-II and OPG had strong model fit for prognostication of the primary pain-related outcome, VAS pain (R 2 =.52). Across diagnostic biomarker panels, a panel including serum MMP-1 and MMP-3 and urine PINP and TIMP-1 had strong model fit as diagnostic biomarkers for %TPI (R 2 =.86). Whereas, a panel including urine CTX-I, CTX-II, IL-8, MMP-2, and TIMP-1 had strong model fit as diagnostic biomarkers for VAS pain (R 2 =.44). Conclusions: Biomarker panels of selected serum and/or urine proteins highly correlate with clinically-relevant metrics for pain and function outcomes in a preclinical model of meniscus allograft transplantation.